A photometric analysis of Abell 1689: two-dimensional multi-structure decomposition, morphological classification, and the Fundamental Plane - Bontà, E; Davies, R; Houghton, R; D’Eugenio, F; Méndez-Abreu, J (Oxford University Press, 2017)
We present a photometric analysis of 65 galaxies in the rich cluster Abell 1689 at z = 0.183, using the Hubble Space Telescope Advanced Camera for Surveys archive images in the rest-frame V band.We perform two-dimensional multicomponent photometric decomposition of each galaxy adopting different models of the surface-brightness distribution. We present an accurate morphological classification for each of the sample galaxies. For 50 early-type galaxies, we fit both a de Vaucouleurs law and a S´ersic law; S0s are modelled by also including a disc component described by an exponential law. Bars of SB0s are described by the profile of a Ferrers ellipsoid. For the 15 spirals, we model a S´ersic bulge, exponential disc and, when required, a Ferrers bar component. We derive the Fundamental Plane (FP) by fitting 40 early-type galaxies in the sample, using different surface-brightness distributions. We find that the tightest plane is that derived by S´ersic bulges. We find that bulges of spirals lie on the same relation. The FP is better defined by the bulges alone rather than the entire galaxies. Comparison with local samples shows both an offset and rotation in the FP of Abell 1689.